Benign lymph node microenvironment is associated with response to immunotherapy. Issue 1 (12th February 2020) - Toki, Maria I; Kumar, Deepika; Ahmed, Fahad S; Rimm, David L; Xu, Mina L
Abstract: Introduction: Benign lymph nodes have been considered the hubs of immune surveillance in cancer patients. The microenvironment of these lymphoid tissues can be immune suppressed, hence allowing for tumor progression. Understanding the spectrum of benign findings in bystander lymph nodes in immune checkpoint blockade therapy could prove to be key to understanding the mechanism and assessing treatment response. Methods: Benign lymph nodes and spleen were evaluated from patients treated with immunotherapy who subsequently received postmortem examination. We used quantitative immunofluorescence (QIF) to assess tumor infiltrating lymphocytes (TIL) and macrophage marker expression and characterized activation status using a novel multiplexed QIF assay including CD3, GranzymeB, and Ki67. We performed immunohistochemistry to correlate results of QIF. Results: Benign lymph nodes from non-responders to immunotherapy showed significantly higher expression of cytotoxic markers and proliferation index (Ki67) in T cells compared to responders. Higher expression of PD-L1 in macrophages was also observed. There was no significant difference in CD3 + expression, but higher levels of CD8 + T cells as well as CD20 + B cells were seen in lymph nodes of non-responders. No significant differences were seen between responder and non-responder splenic tissue. Findings were supported by traditional immunostaining methods. Conclusions: While most studies in biomarkers for immunotherapy focus on tumor microenvironment, we show that benign lymph node microenvironment may predict response to immunotherapy. In responding patients, bystander lymph nodes appear to have been mobilized, resulting in reduced cytotoxic T cells. Conversely, patients whose disease progressed on immunotherapy demonstrate higher levels of macrophages that express increased PD-L1, and activated T cells not recruited to the tumor site.